Wood dust exposure and risk of sinonasal cancer development - Alicja Maria Ozga; Aleksandra Obuchowska; Arkadiusz Standyło; Justyna Wójcik; Karolina Obuchowska (Kazimierz Wielki University, 2020)
Introduction: The incidence of sinonasal cancers (SNCs) is quite rare; they contribute to 0,16% of all malignant tumors and to 3% among head and neck cancers. The survival rate remains poor - it is 59.5% for 5 years. The two most common subtypes are squamous-cell carcinoma (SCC) and adenocarcinoma (ADC). Both subtypes of SNC are associated to occupational exposures. Main risk factors for SNC include chemical components, wood and textile dusts, nickel and chromium, welding fumes. Thus, people doing particular jobs are at higher risk of SNC.    Purpose:  Evaluation of the influence of wood dust on SNCs development.   Materials and methods:  We performed a database research using Pubmed, Google Scholar, Springer Link and ResearchGate and we made review and meta-analysis of relevant studies. We searched for studies analyzing the relationship between wood dust and sinonasal cancer incidence.   Results:  Studies have shown that the risks of SNCs were great for workers in wood-related jobs, especially cabinetmaking, carpentry or joinery. There was a strong correlation between ADC incidence and wood dust, however the morbidity for SCC was also high.   Conclusions:  SNCs development is related to the occupational exposures. People engaged in jobs associated with wood processing are at great risk. Proper ventilation and protection is necessary while doing wood-related jobs.   Key words: wood dust; nasal sinus carcinoma; occupational exposure; ADC